ROLLOVER PREVENTION SYSTEM OF TRUCK-TRAILER VEHICLE USING STEERABLE-WHEEL FOR MIDDLE AXLE - Muhammad Nadwi Hakimi Adnan (Tesis, 2021)
This study shows that the proposed steerable-wheel system was proven managed to reduce the unwanted lateral, yaw and roll motions by producing the appropriate wheel steer angle for middle axle to maintain the manoevrability and stability of the single-trailer truck from rollover accident.